Social networking behaviour and psychological distress among Malaysian undergraduates during the COVID-19 pandemic - Teh, Liang Jing; Wong, Su Luan (International Journal of Public Health Science (IJPHS), 2024)
This study investigated the extent of social networking sites usage and its relationship with the undergraduate students’ psychological distress during the COVID-19 pandemic. In this quantitative correlational study, 212 students completed questionnaires assessing their social networking site use and psychological distress. Descriptive analysis revealed that the students were avid users of social networking sites. On average, almost half of the students used social networking sites more than six times per day while more than onethird of them spent more than three hours each day using social networking sites. Findings also showed that entertainment was the primary purpose of social networking site usage, followed by academic, social, and informational uses. Notably, nearly half of the students reported high levels of anxiety, and approximately one-third experienced significant depression and stress. However, correlational analyses found no significant associations between the length, frequency, and all purposes (social, academic, information, or entertainment) of social networking site usage and the levels of depression, anxiety, and stress. These findings suggest a complex interplay between these variables. Given the ever-increasing use of social networking sites and the alarming prevalence of mental distress among students, further studies are needed to delve deeper into this multifaceted relationship.